Glocalism. Ten years of culture, politics and innovation - Bassetti, Piero (Milano University Press, 2024)
"Glocalism: Journal of Culture, Politics and Innovation" is a peer-reviewed, open access and cross-disciplinary journal that aims at stimulating increasing awareness and knowledge around the new dynamics that characterize glocal reality. A journal on glocalism, which corresponds with the very concept of being glocal and is recognized in a global-academic context, can only be available online. After ten years of life, though, the editors have decided to select, collect and publish on paper some articles that are more representative than others, in order to summarize and show the richness and depth which distinguished the activity of "Glocalism" so far and which will mark its future issues online at https://riviste.unimi.it/index.php/glocalism